Emotional Intelligence as Predictor of Mental Health in Hospital Nurses, Pakistan: Emotional Intelligence and Mental Health - Aisha, .; Ahmad, Riaz; Ali, Uzma (Pakistan Journal of Health Sciences, 2023)
Background: Emotional intelligence is a tool, as is the ability to understand, perceive, manage and utilize information. Therefore, an emotionally intelligence people could control their stressors and improve the individual’s productivity at the workplace. Emotional intelligence is a tool, as is the ability to understand, perceive, manage and utilize information. Therefore, an emotionally intelligence people could control their stressors and improve the individual’s productivity at the workplace. Objective: To explore the relationship of emotional intelligence and mental health in female hospital nurses in Pakistan. Methods: The correlational design was used in this study. The sample comprised of (N=217) hospital nurses with the age range of 20 years to 45 years (Mean age=29.98; SD=6.37) were selected through systematic randomization procedure from different public hospitals of Hyderabad. The data collection was gathered about 8 months from January 2019 August 2019. The demographic Form, Trait Emotional Intelligence, Pakistani Urdu translated version (TEIQue-SF) & Aga Khan University Anxiety Depression Scale were used. Results: The results showed a significant predictive relationship of emotional intelligence with mental health of hospital registered female nursing (R²= .374, p< .001). Conclusions: The hospital nurses (who have high emotional intelligence) suffer less from mental health problems and are at low risk of anxiety and depression Methodology: The Correlational design was used in this study. The sample comprised of (N=217) hospital nurses with the age range of 20 years to 45 years (Mean age=29.98; SD=6.37) were selected through systematic randomization procedure from different Public hospitals of Hyderabad. The data collection was gathered about 8 months from January 2019 August 2019. The demographic Form, Trait Emotional Intelligence, Pakistani Urdu translated version (TEIQue-SF) & Aga Khan University Anxiety Depression Scale were used. Results: The results showed a significant predictive relationship of emotional intelligence with mental health of hospital registered female nursing (R²= .374, p< .001). Conclusion: The hospital nurses (who have high emotional intelligence) suffer less from mental health problems and are at low risk of anxiety and depression. Keywords: Emotional Intelligence, Mental Health, Hospital Nurses